2015
DOI: 10.4103/2249-4863.161336
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetes and pre-diabetes and assessments of their risk factors in urban slums of Bangalore

Abstract: Background:To determine the prevalence of diabetes and pre-diabetes and to assess the risk factors associated with diabetes and pre-diabetes in the urban slums of Bangalore.Materials and Methods:A cross-sectional study was conducted in four slums of Bangalore in the age group of 35 years and above comprising of total 2013 subjects. Risk factors like age, sex, family history, behavior, physical activity, BMI, waist hip ration, diet habits were assessed to find their association with diabetes.Results:Prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 28 publications
4
32
3
Order By: Relevance
“…Prevalence of diabetes was 12.33% in urban Bengaluru as detected by blood glucose testing which is almost similar to our study findings. 13 The prevalence of raised blood glucose was found to be 9% by Rathod. 14 Though lot of efforts were made to motivate the individuals to undergo further confirmation test, only 1 amongst the 44 individuals with raised blood glucose underwent confirmatory test. In a study conducted by Shewade where OPD patients were screened for raised blood glucose, they found that the screening yielded only 3.5% case detection rate, because of poor compliance to confirmatory tests.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of diabetes was 12.33% in urban Bengaluru as detected by blood glucose testing which is almost similar to our study findings. 13 The prevalence of raised blood glucose was found to be 9% by Rathod. 14 Though lot of efforts were made to motivate the individuals to undergo further confirmation test, only 1 amongst the 44 individuals with raised blood glucose underwent confirmatory test. In a study conducted by Shewade where OPD patients were screened for raised blood glucose, they found that the screening yielded only 3.5% case detection rate, because of poor compliance to confirmatory tests.…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that Asian Indians are more susceptible to adiposity (based on BMI), and central obesity, despite having a relatively low BMI [13]. We did not get any gender difference in prevalence of diabetes and pre-diabetes, though a South Indian study reported greater prevalence in females, which they ascribed to increased central obesity in females [14]. In our study, 306 individuals had co-existent DM and hypertension, pointing towards the close association between the two important cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 47%
“…The variables which have statistically potential association were entered into multiple logistic regression model. This study got the result that, prevalence of diabetes was 12.33% and of prediabetes was 11.57% and they showed statistically significant association with prevalence of diabetes and prediabetes factors such as increasing age, over weight and obesity, sedentary lifestyle, tobacco consumption, and diet habits [3].…”
Section: Introductionmentioning
confidence: 92%